1991
DOI: 10.1136/jnnp.54.9.807
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral effects of arecoline in patients with autonomic failure.

Abstract: Increased plasma adrenalin (A) levels following arecoline in normal subjects and patients with multiple system atrophy (MSA) may result from nicotinic adrenal stimulation. Lack of this response in patients with pure autonomic failure (PAF) is consistent with peripheral sympathetic dysfunction. The mechanisms underlying diminished plasma corticotropin (ACTH) responses to arecoline may differ in patients with autonomic failure. Hypothalamic, cholinergic degeneration could prevent the response in MSA whereas pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The adreno-medullary response to hypoglycaemia, for example, requires activation of central glucose receptors and an efferent pre-ganglionic sympathetic arc [23]. This response is blunted in both PAF and MSA, but can be restored in MSA subjects through the application of post-ganglionic stimuli [28]. The pressor response to a low-dose CO 2 challenge was lost in MSA subjects compared to controls presumably due to impaired or absent responses of sympathetic autonomic nervous system structures in the brainstem or cervical trunk [5].…”
Section: Discussion J Neuroendocrine Responsementioning
confidence: 97%
“…The adreno-medullary response to hypoglycaemia, for example, requires activation of central glucose receptors and an efferent pre-ganglionic sympathetic arc [23]. This response is blunted in both PAF and MSA, but can be restored in MSA subjects through the application of post-ganglionic stimuli [28]. The pressor response to a low-dose CO 2 challenge was lost in MSA subjects compared to controls presumably due to impaired or absent responses of sympathetic autonomic nervous system structures in the brainstem or cervical trunk [5].…”
Section: Discussion J Neuroendocrine Responsementioning
confidence: 97%
“…It has been reported that arecoline increases plasma epinephrine levels in normal subjects and patients with multiple system atrophy, which may result from nicotinic adrenal stimulation [18] . Therefore, in order to compare the effects of nicotine with those of arecoline, it was of interest to examine the effect of nicotine on CA secretion from isolated perfused rat adrenal glands evoked by ACh, high K + , and DMPP.…”
Section: Effect Of Nicotine On Ca Secretion Evoked By Ach Excess K +mentioning
confidence: 99%
“…It has been concluded that the pressor effects brought about by quaternary compounds can be attributed to the stimulation of nicotinic and muscarinic receptors in the sympathetic ganglia of both pithed and anesthetized rats [17] . Moreover, Polinsky and coworkers found that the increased plasma epinephrine levels following arecoline treatment in normal subjects and patients with multiple system atrophy might result from nicotinic adrenal stimulation [18] . It has also been reported that betel chewing increases plasma concentrations of norepinephrine and epinephrine [19] .…”
mentioning
confidence: 99%
“…Arecoline causes a reduction in the level of norepinephrine level in the cortex and subcortex of mice (22). Plasma epinephrine level is also increased after arecoline treatment in normal human subject (23). Betel nut chewing increases plasma concentrations of norepinephrine and epinephrine in humans (24).…”
Section: Introductionmentioning
confidence: 97%